The Value of Biological and Conditional Factors for Staging of Patients with Resectable Pancreatic Cancer Undergoing Upfront Resection: A Nationwide Analysis - Thijs J. Schouten; Iris W.J.M. van Goor; Galina Dorland; Marc G. Besselink; Bert A. Bonsing; Koop Bosscha; Lodewijk A.A. Brosens; Olivier R. Busch; Geert A. Cirkel; Ronald M. van Dam; Sebastiaan Festen; Bas Groot Koerkamp; et al. (2024)
Abstract Background Novel definitions suggest that resectability status for pancreatic ductal adenocarcinoma (PDAC) should be assessed beyond anatomical criteria, considering both biological and conditional factors. This has, however, yet to be validated on a nationwide scale. This study evaluated the prognostic value of biological and conditional factors for staging of patients with resectable PDAC. Patients and Methods A nationwide observational cohort study was performed, including all consecutive patients who underwent upfront resection of National Comprehensive Cancer Network resectable PDAC in the Netherlands (2014–2019) with complete information on preoperative carbohydrate antigen (CA) 19-9 and Eastern Cooperative Oncology Group (ECOG) performance status. PDAC was considered biologically unfavorable (R B+ ) if CA19-9 ≥ 500 U/mL and favorable (R B− ) otherwise. ECOG ≥ 2 was considered conditionally unfavorable (R C+ ) and favorable otherwise (R C− ). Overall survival (OS) was assessed using Kaplan–Meier and Cox-proportional hazard analysis, presented as hazard ratios (HRs) with 95% confidence interval (CI). Results Overall, 688 patients were analyzed with a median overall survival (OS) of 20 months (95% CI 19–23). OS was 14 months (95% CI 10 months—median not reached) in 20 R B+C+ patients (3%; HR 1.61, 95% CI 0.86–2.70), 13 months (95% CI 11–15) in 156 R B+C− patients (23%; HR 1.86, 95% CI 1.50–2.31), and 21 months (95% CI 12–41) in 47 R B−C+ patients (7%; HR 1.14, 95% CI 0.80–1.62) compared with 24 months (95% CI 22–27) in 465 patients with R B−C− PDAC (68%; reference). Conclusions Survival after upfront resection of anatomically resectable PDAC is worse in patients with CA19-9 ≥ 500 U/mL, while performance status had no impact. This supports consideration of CA19-9 in preoperative staging of resectable PDAC.